Grazing intensity levels influence C reservoirs of wet and mesic meadows along a precipitation gradient in Northern Patagonia - Enriquez, Andrea Soledad; Chimner, Rodney Allen; Cremona, Maria Victoria; Diehl, Paula; Bonvissuto, Griselda (Springer, 2018)
Wet meadows are important ecosystems for forage production and as carbon reservoirs in semi-arid areas. In Patagonia, Argentina, large areas of wet meadows have been classified as overgrazed by livestock. The objective of this study was to determine whether long-term overgrazing has affected carbon (C) storage in plant and soil pools in wet and mesic meadows. The study occurred in Northern Patagonia, in three study sites located along a precipitation gradient. Our results indicate that long-term overgrazing reduced, on average, 35 % of the total ecosystem C pool. There was significantly lower aboveground and belowground plant production in heavily grazed compared to lightly grazed sites, 419 ± 262 – 128 ± 110 g m2 year−1 and 3796 ± 2622 – 1702 ± 1012 g m2 year−1, respectively. Soil C concentrations were also less in heavily grazed sites (184 ± 98 – 105 ± 58 g kg−1 at 1 m depth, respectively). The response of meadows to long-term heavy grazing also appears to be influenced by different levels of precipitation, with sites in drier areas being apparently more susceptible to overgrazing. Our results indicate that new management and restoration practices are needed to stop and reverse meadow deterioration in degraded meadows of Northern Patagonia.